LAW ENFORCEMENT ON THE CRIMINAL ACTS OF SERIOUS ABUSE BY CHILDREN TO CHILDREN - Lidansyah, Wendy; Wiryadi, Uyan; Sinaga, Parbuntian (JILPR Journal Indonesia Law and Policy Review, 2024)
This study aims to analyze the qualifications of criminal acts of physical violence against children based on legislation and to analyze the application of criminal law in criminal acts of physical violence against children in Decision Number 19/Pid.Sus-Anak/2018/PN Jkt.Pst., and Decision Number 00/Pid.Sus-Anak/2023/PN Jkt.Brt. The type of research used by the author is a type of normative legal research with a legislative approach method, a case approach, and a conceptual approach. The legal materials used consist of primary legal materials, namely laws and regulations, and judges' decisions. Secondary legal materials, namely journals and book literature related to this study. As well as tertiary legal materials, namely articles and literature on the internet as supporting data in this study. All of these legal materials are analyzed qualitatively and presented descriptively. The results of this study are, 1) The qualification of the crime of physical violence against children based on statutory regulations is an act that is included in Article 80 Paragraph (1) of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection concerning physical violence committed against children as victims and in the general scope. 2) The application of criminal law in Decision Number 19/Pid.Sus-Anak/2018/PN Jkt.Pst., and Decision Number 00/Pid.Sus-Anak/2023/PN Jkt.Brt., is correct. The defendant has been proven legally and convincingly to fulfill the elements in Article 80 Paragraph (1) of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. The judge considered that the defendant could be held responsible for the actions he had committed because he was in good health when he committed the crime, and there was no reason to remove the criminal sentence, so the Panel of Judges sentenced the Defendants to imprisonment.